The Art of Translating Indonesian Folklore: A Case Study of “Hasil Sebuah Kejujuran” by Bambang Subagyo” - Latranita, Elsa; Sembiring, Milisi; sitinjak, Vivi Novalia (Journal of Applied Linguistics, 2024)
This study used translation techniques to translate the source language into the target language and analyzed cultural terms in translating the Indonesian folklore "Hasil Sebuah Kejujuran" from Indonesian to English. Based on the issues, the study sought to categorize and identify the cultural words from the source language (SL) into the target language (TL), as well as to identify and describe the translation methods that were employed. The descriptive-qualitative method was the research approach employed. The information utilized comes from the translation of Indonesian cultural phrases from the folklore into English. Up to eighteen data in Indonesian cultural phrases were found in this investigation. There are two data points (11,10 %) of society and up to 16 data points (88,90 %) relating to cultural terminology and language and communication. The following translation methods were employed to translate the cultural words into English: literal, up to 6 data points (33, 30%), couplets, up to 1 (5, 60%), and description, up to 11 (61, 10%). Keywords : Cultural_Terms; Translation_Techniques; Indonesian_Folklore